2021
DOI: 10.3389/fgene.2021.671976
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Epigenetics, and Gender Impact in Axial-Spondyloarthritis Susceptibility: An Update on Genetic Polymorphisms and Their Sex Related Associations

Abstract: Spondyloarthritis (SpA) is a group of chronic inflammatory rheumatic disease that can be divided into predominantly axial or predominantly peripheral involvement, with or without associated psoriasis, inflammatory bowel disease or previous infection. Axial SpA (axSpA) encompasses ankylosing spondylitis (AS) with radiological sacroiliitis, and a type without radiographic sacroiliitis, called “non-radiographic axial SpA” (nr-axSpA). Males and females show large differences in their susceptibility to SpA, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 118 publications
1
8
0
1
Order By: Relevance
“…The differences observed in class I HLA alleles between axPsA and r-axSpA were consistent with previous reports demonstrating that axPsA and r-axSpA overlap with respect to the contribution of HLA-B27 but also have distinct genetic risk factors [ 1 , 24 ]. Previous studies have reported that approximately 80% of patients with r-axSpA are HLA-B27- positive [ 25 , 26 ], whereas approximately 20% of patients with axPsA are HLA-B27- positive [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…The differences observed in class I HLA alleles between axPsA and r-axSpA were consistent with previous reports demonstrating that axPsA and r-axSpA overlap with respect to the contribution of HLA-B27 but also have distinct genetic risk factors [ 1 , 24 ]. Previous studies have reported that approximately 80% of patients with r-axSpA are HLA-B27- positive [ 25 , 26 ], whereas approximately 20% of patients with axPsA are HLA-B27- positive [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Ankylosing spondylitis (AS) is an inflammatory AID causing spondyloarthritis of the spine and sacroiliac joints and prevalent mainly in men with a ratio of 10:1 at the age of 20–30 years old in respect to women ( Chimenti et al, 2021 ). Because the exact pathology of AS is still unclear, there are incoming data about the relationship between CNVs of these genes and AS, including CCL3L1 , FCGR3A , FCGR3B , TLR7 , UGT2B17 , BMP8A , and so on.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA) is a type of systemic inflammatory arthritis, which presents with joint and extra-articular symptoms such as inflammatory bowel disease ( 1 ). The most well-known marker gene for axSpA is HLA-B27, and several other genes are known to be associated with axSpA pathogenesis ( 2 ). In addition, environmental factors are known to play a role in inducing axSpA ( 1 ).…”
Section: Introductionmentioning
confidence: 99%